Trichoderma inoculants and straw compost improved resilience and yield in Cu-contaminated rice paddies - Virginia Cuevas; Charina Gracia Banaay (Nusantara Bioscience, 2022)
Abstract. Cuevas VC, Banaay CGB. 2022. Trichoderma inoculants and straw compost improved resilience and yield in Cu-contaminated rice paddies. Nusantara Bioscience 14: 1-9. Rice paddies in Marinduque, Philippines, are copper-contaminated from tailings of two mining companies formerly operating in the province. At present, paddy-soil copper concentration ranges from 22-386 mg kg-1. Crops suffer from copper toxicity and water stress due to climate-related events. The field study investigated the ability of in situ composted rice straw and Trichoderma microbial inoculant (TMI) to mitigate rice productivity constraints. In treated set-ups, rice straw was scattered on the paddy after harvest. Triple 14 mineral fertilizer was mixed with Trichoderma compost activator, broadcasted over the straws, and subsequently incorporated into the soil during land preparation. Rice seeds were TMI-coated before sowing. Rice straw composting was not done in control set-ups, and seeds were uncoated. Mineral fertilizers were applied to both set-ups. Furthermore, set-ups were categorized based on soil Cu content, such as normal, moderate, and high. Four replicates were made per season and category. Rice leaves did not show yellowing in treated paddies, indicating adequate N mineralization and plant uptake. The difference in yield was significantly higher (81%) in treated paddies compared to the control. During severe drought conditions, the mean yield in treated paddies was 1.8 t ha-1, while that of control paddies was zero. The yield was significantly correlated with K inputs, mainly by compost in treated paddies. Applying rice straw compost and Trichoderma inoculants can be an adaptive strategy for climate change resilience and mitigation of copper toxicity in crops.